Training youth and adult workers in the Benta Pereira Public High School: A reflection based on Salesian Pedagogy - María de Fátima Fernándes Coelho (Universidad Politécnica Salesiana, 2013)
This study is due to analyze the experience in the Education of Young and Adults from Benta Pereira State School in the city of Campos dos Goytacazes / RJ, Brazil in light of the Salesian Pedagogy. First it has been resumed the right of education and the preparation for work, as long as guiding principles of the Salesian Pedagogy, by comparing with the legal frameworks of the Education among young and adult people, to verify if the humanistic approach present in the first one was also considered by the institution. To this stud,y Bibliographical research, questionnaires and interviews have been used. The research roots are the following categories: the right to education, jog training and the Salesian Pedagogy. From this investigation, the results pointed to develop actions to improve the educational activities and educational management in the light of that pedagogy, which includes the pedagogical and methodological development with a humanist bias and effective opportunities to promote professional training in the binomial and citizenship.